Students, Police, and the School-To-Prison Pipeline - Jason P. Nance (Washington University Law Review, 2016)
Since the terrible shootings at Sandy Hook Elementary School in Newtown, Connecticut, lawmakers and school officials continue to deliberate over new laws and policies to keep students safe, including putting more police officers in schools. Yet these decisionmakers have not given enough attention to the potential negative consequences that such laws and policies may have, such as creating a pathway from school to prison for many students. Traditionally, only educators, not law enforcement, handled certain lower-level offenses that students committed, such as fighting or making threats without using a weapon. Drawing on recent restricted data from the US Department of Education, this Article presents an original empirical analysis revealing that a police officer’s regular presence at a school is predictive of greater odds that school officials refer students to law enforcement for committing various offenses, including these lower-level offenses. This trend holds true even after controlling for: (1) state statutes that require schools to report certain incidents to law enforcement; (2) general levels of criminal activity and disorder that occur at schools; (3) neighborhood crime; and (4) other demographic variables. The consequences of involving students in the criminal justice system are severe, especially for students of color, and may negatively affect the trajectory of students’ lives. Therefore, lawmakers and school officials should consider alternative methods to create safer learning environments.
Keywords: Law enforcement; School law enforcement; Zero tolerance policy; Juvenile justice; Juvenile Law; Constitutional Law; Criminal Law